Silica-Supported Nitrogen-Enriched Porous Benzimidazole-Linked and Triazine-Based Polymers for the Adsorption of CO2 - Maruthapandi, Moorthy; Eswaran, Lakshmanan; Cohen, Reut; Perkas, Nina; Luong, John H. T; Gedanken, Aharon (Langmuir, 2020)
Two crystalline and five amorphous benzimidazole polymers (BINP) were synthesized and conjugated to porous silica via amine and aldehyde-based materials by a simple reflux procedure. The resulting polymers were subject to thermal analysis for monitoring and quantification of the adsorption and desorption of CO2. All the polymers were capable of adsorbing CO2 from a flowing stream of only 80 mL/min at 25 °C. The adsorbed CO2 onto the polymers were effectively desorbed at room temperature, illustrating the potential application of such polymers for repeated adsorption/desorption of CO2. The CO2 adsorption capacities of these polymers were dependent upon their nitrogen content, specific surface area, and pore size. The available nitrogen atoms for binding to the carbon of CO2 via tetrel bonds also plays an important role in the capture of this gas. Minimal and much lower CO2 adsorption was also noted with two crystalline polymers, compared to the five amorphous counterparts. Intermolecular hydrogen bonding and π–π interaction effectively prevented the polymer N sites of the crystalline polymers from interacting with polarized CO2 molecules.